Exploration of Christian Women’s Vocational Ministry Leadership and Identity Formation in Evangelical Churches on the West Coast - Glanz, Judy L. (Christian education journal, 2020)
This empirical research explores adult identity formation through work experiences, gaining insight into structures and practices which allow women to thrive in leadership within the evangelical church ministry context. This qualitative research explores adult identity formation and gender role stereotypes in leadership domains within the evangelical church context on the West Coast. Twenty-five (n = 25) women in vocational church leadership, aged 25-71, revealed what impedes or contributes to female leadership adult identity formation. Key findings revealed women leaders thrive and gain identity strength through agency found in union with Christ; hold back identity components and skills available to church leadership teams to fit the male work context; contextual factors impact women’s well-being in leadership including assumptions and mindsets adverse to women leading; and lead pastors and supervisors’ beliefs about women in leadership are critical to healthy identity formation. Therefore, this research is an exploration of what experiences assist women leaders to thrive or not thrive in evangelical vocational leadership on the West Coast and how their identity in Christ empowers their leadership.